Balsių kiekybės sistemų sankirta ir raida - Grumadienė, Laima (Baltistica, 1994)
INTERSECTION AND DEVELOPMENT OF THE VOWEL QUANTITY SYSTEMS Under the intersection of two dialectal systems – Southwest (A) and East (B) Lithuanian – the urban Lithuanian system C comes into being. In the latter, vowel length dephonologization is obvious and predicted because of the essential quantitative and qualitative differences existing in both A and B systems. The synchronic alternation there is considered as an indicative of diachronic change in progress.